Internal polarized deuterium target with cryogenic atomic beam source; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 495, № 1 - Dyug M. V.; Isaeva L. G.; Lazarenko B. A.; Mishnev S. I.; Nikolenko D. M.; Rachek I. A.; Shestakov Y.V.; Sadykov R. S.; Toporkov D. K.; Zevakov S. A.; Osipov A.V.; Stibunov V. N. Victor Nikolaevich (2002, 2002)
В фонде НТБ ТПУ отсутствует